2010
DOI: 10.2214/ajr.09.3702
|View full text |Cite
|
Sign up to set email alerts
|

Axial Oblique CT to Assess Femoral Anteversion

Abstract: Axial oblique reformations allow more accurate anteversion assessment than axial images with femoral flexion, extension, and internal and external rotation. Centers should consider replacing the standard straight axial technique with the axial oblique method for CT determination of femoral anteversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 9 publications
3
76
4
1
Order By: Relevance
“…A tangent line is drawn between the posterior peaks of the femoral condyles. [ 2 , 3 , 7 , 12 ] Previous research has shown that this method provides the best reproducibility. [ 9 ] This method was not modified, in order to ensure comparability with previously published data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tangent line is drawn between the posterior peaks of the femoral condyles. [ 2 , 3 , 7 , 12 ] Previous research has shown that this method provides the best reproducibility. [ 9 ] This method was not modified, in order to ensure comparability with previously published data.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have described femoral anatomy in cadavers [ 5 , 7 , 10 , 12 ] and have used techniques including plain radiography [ 1 , 5 , 11 ], computed tomography [ 7 , 9 ], 3D-reconstructed computed tomography [ 14 ] and MRI [ 21 ]. Although extensive research has been performed, results vary over a comparatively large range, which indicates that there are persistent difficulties in carrying out exact measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Where scans are not aligned with the femoral shaft axis, calculation may be needed to transform the torsion to a reference plane, as positioning-related measurement errors can be as large as 8.8° (Hermann and Egund, 1997). After 3D rendering of the proximal femur it is possible to take an oblique slice along the femoral neck angle in the coronal plane (Kim et al, 2000b;Jarrett et al, 2010) or compute the femoral neck axis in 3D (Sugano et al, 1998a;Kim et al, 2000a;Lee et al, 2006;Berryman et al, 2014). The distal femoral axis can be evaluated with one single axial slice with reference to one of the axes described earlier.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…The true neck shaft angle and anteversion were derived using the formula, and the results were compared with those determined using computed tomography, in which the anteversion was measured using the axial oblique plane (parallel to the femoral neck axis) and the transcondylar plane. 16 The formula was based on trigonometry. When the femur rotates along its shaft axis, the neck shaft angle eventually becomes a straight line in the anteroposterior view.…”
Section: Methodsmentioning
confidence: 99%